Impact evaluation report: Egypt’s Forsa graduation program - Gilligan, Daniel O.; Kurdi, Sikandra; Tabe-Ojong, Martin Paul; Yassa, Basma (International Food Policy Research Institute, 2022)
Forsa, which means “Opportunity” in Arabic, is a new economic inclusion program of the government of the Arab Republic of Egypt. Implemented by the Ministry of Social Solidarity, the program aims to graduate beneficiaries of the national cash transfer program, the Takaful & Karama Program (TKP), to economic self-reliance by enabling them to engage in wage employment or sustainable economic enterprises. The 2021 World Bank Economic Inclusion report (Andrews et al. 2021) highlights a recent increase globally in such graduation or economic inclusion programs, which now reaches around 92 million beneficiaries from 20 million households across more than 75 countries. This rapid growth has necessitated an increasing demand for evidence on best practices in graduation program implementation. The newly designed Forsa program is based on the graduation approach, but with innovations drawing from theories of behavioral economics as well as creating a network of active youth volunteers for economic empowerment to reduce costs compared to the standard BRAC-inspired model. Forsa also expands the graduation model to include the option of wage-employment, rather than only focusing on self-employment. Evidence on the impact of job training programs linked to wage employment on both job retention and future earnings is mixed (McKenzie 2017), although most such programs do not include cash assistance. This impact evaluation of the Forsa program in Egypt is intended to contribute to the global evidence on effective graduation program design as well as provide immediate policy-relevant guidance for the Ministry of Social Solidarity. The impact evaluation will measure the degree to which Forsa is successful at increasing household consumption and will investigate which participant groups and program features demonstrate the greatest improvements in household welfare and economic activity.